PENINGKATAN KEAKTIFAN SISWA DALAM PEMBELAJARAN IPA MELALUI PENDEKATAN COOPERATIVE TIPE NUMBERED HEAD TOGETHER PADA SISWA KELAS V SD NEGERI 2 BUWARAN MAYONG JEPARA (Improving Students’ Activity in Learning Science through Cooperative Approach: Type Numb (Universitas Negeri Semarang, 2010)
The backgrounds of the research were the lack of students’ activity in learning science, students’ dissatisfactory achievement, and the lack of learning media. Numbered Head Together cooperative approach (NHT) model was used to overcome those problems. Subject of the research were the students of year V Buwaran 2 State Primary School. This belonged to classroom action research with steps of planning, acting, observing, and reflecting. The research results showed that obtained average score on students’ activity tended to improve significantly. At the first cycle, the average score was 59%, second cycle was 79%, and the third one was 90%. The next result was that teacher’s activity also improved. The average score in sequence was 78% at cycle 1, 88% at cycle 2, and 95% at the last cycle. The third result of the research was that students’ achievement also improved. They got average score 60% at cycle one, 75% at cycle two and 95% at the last one. So that based the data, it could be concluded that NHT Cooperative approachcould improve activity of the fifth grade students of Buwaran 2 State Primary School. Keywords: students’ activity in learning science